Characteristics Of Childhood Tuberculosis Patients At La Palaloi Maros Regional Hospital - Andi We Yada Tenribali; Muh Alfian Jafar; Wahida Ratnawati; Andi Husni Esa Darussalam; Nikmawati, Nikmawati (Sean Institute, 2024)
Pulmonary tuberculosis (TB) is a disease caused by Mycobacterium tuberculosis. Knowing the frequency of characteristics of childhood tuberculosis at La Palaloi Maros Regional Hospital. This research uses a cross-sectional method which is descriptive retrospective with a total sampling technique. The population covered by this study were all pediatric patients diagnosed with TB at La Palaloi Maros Regional Hospital. The results of the study showed that, of the 50 people suffering from tuberculosis, based on immunization history, the most cases occurred in children who did not have a history of BCG immunization, namely 30 people (60.00%), TB contact history occurred most often in children who had a history of contact. TB is 33 people (66.00%), gender is most common in children with male gender, namely 30 people (60.00%), age is most common in children aged >5 years, namely 27 people (54.00%), nutritional status was most common in children with normal nutritional status, namely 27 people (54.00%). The characteristics of Tuberculosis sufferers at La Palaloi Maros Regional Hospital in 2021, those who most often experience Tuberculosis are those who do not have a history of BCG immunization, have a history of contact, male gender, age > 5 years, and normal nutritional status.